Glutamate levels and perfusion in pons during migraine attacks: A 3T MRI study using proton spectroscopy and arterial spin labeling. Issue 3 (March 2021) - Younis, Samaira; Christensen, Casper E; Vestergaard, Mark B; Lindberg, Ulrich; Tolnai, Daniel; Paulson, Olaf B; Larsson, Henrik BW; Hougaard, Anders; Ashina, Messoud
Migraine is a complex disorder, involving peripheral and central brain structures, where mechanisms and site of attack initiation are an unresolved puzzle. While abnormal pontine neuronal activation during migraine attacks has been reported, exact implication of this finding is unknown. Evidence suggests an important role of glutamate in migraine, implying a possible association of pontine hyperactivity to increased glutamate levels. Migraine without aura patients were scanned during attacks after calcitonin gene-related peptide and sildenafil in a double-blind, randomized, double-dummy, cross-over design, on two separate study days, by proton magnetic resonance spectroscopy and pseudo-continuous arterial spin labeling at 3T. Headache characteristics were recorded until 24 h after drug administrations. Twenty-six patients were scanned during migraine, yielding a total of 41 attacks. Cerebral blood flow increased in dorsolateral pons, ipsilateral to pain side during attacks, compared to outside attacks (13.6%, p = 0.009). Glutamate levels in the same area remained unchanged during attacks (p = 0.873), while total creatine levels increased (3.5%, p = 0.041). In conclusion, dorsolateral pontine activation during migraine was not associated with higher glutamate levels. However, the concurrently increased total creatine levels may suggest an altered energy metabolism, which should be investigated in future studies to elucidate the role of pons in acute migraine.